1981
DOI: 10.1007/bf00344645
|View full text |Cite
|
Sign up to set email alerts
|

Relative growth rates and the grazing optimization hypothesis

Abstract: A mathematical analysis of the changes in plant relative growth rates necessary to increase aboveground production following grazing was conducted. The equation derived gives an isoline where production of a grazed and ungrazed plant will be the same. The equation has four variables (mean shoot relative growth rate, change in relative growth rate after grazing, grazing intensity, and recovery time) and may be analyzed graphically in a number of ways.Under certain conditions, small increases in shoot relative g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
271
7
2

Year Published

1990
1990
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(301 citation statements)
references
References 20 publications
21
271
7
2
Order By: Relevance
“…However, simulation models have shown that biomass, grazing pressure and nutrient cycling may all interact and result in the enhancement of NAPP (Hilbert et al 1981;Dyer, DeAngelis & Post 1986), but to test the results of these simulations under field conditions is extremely difficult. In addition, the availability of forage and the phenology of plant growth must be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, simulation models have shown that biomass, grazing pressure and nutrient cycling may all interact and result in the enhancement of NAPP (Hilbert et al 1981;Dyer, DeAngelis & Post 1986), but to test the results of these simulations under field conditions is extremely difficult. In addition, the availability of forage and the phenology of plant growth must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The herbivore-optimization model (Dyer 1975;McNaughton 1979McNaughton , 1983aHilbert et al 1981;Dyer et al 1982) describes the effects of increasing grazing pressure on plant production as well as on plant fitness (Paige & Whitham 1987). The model predicts that one of the effects of moderate levels of herbivory on plant production is the enhancement of net primary production of forage plants above that of ungrazed plants.…”
Section: Introductionmentioning
confidence: 99%
“…However, 90% of useable grasslands are degraded because of over-grazing, improper reclamation and adverse effects of droughts exacerbated by climate change (Li 1999;Liu et al 2002;MEP 2006;Li et al 2008;Yang 2010). Many studies have shown that lower stocking rates are necessary for rehabilitating degraded rangelands (Ellison 1960;Hilbert et al 1981;Dyer et al 1986;Kaiser 1998;Kemp and Michalk 2007;Zheng et al 2011). In order to remediate grassland degradation, the government has proposed the 'balancing animals and grass' policy.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated, based on a cellular automaton model that an intermediate frequency of disturbance facilitated the coexistence of competitively superior and fugitive species, while maximizing the equilibrium population size of the inferior species. It has also been shown that an intermediate intensity of grazing may maximize plant productivity through the acceleration of a system's nutrient cycling (McNaughton 1979;Hilbert et al 1985;Loreau 1995;.…”
Section: Introductionmentioning
confidence: 99%